2019
DOI: 10.3390/pathogens8040219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Opportunistic Infections—Toxoplasmosis and Cytomegalovirus Infection in HIV-Infected Patients in Slovakia

Abstract: : The HIV/acquired immunodeficiency syndrome (AIDS) pandemic has affected the health status of the population in many countries. Early symptomatic HIV infection includes persistent generalized lymphadenopathy (PGL), which can be associated with opportunistic infections, e.g., toxoplasmosis and Cytomegalovirus (CMV) infection. This study followed the occurrence of PGL, toxoplasmosis, and Cytomegalovirus infection in 32 HIV-positive patients and analyzed the clinical signs of disease in relation to the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The seropositivity rate recorded in this study was lower than that in HIV-positive patients from Slovakia examined in 2019 (34.4%) [43], and also lower than the pooled prevalence of latent toxoplasmosis calculated for Europe (41.1%) in the systematic review of studies published by Rostami et al [44]. Since the seropositivity to T. gondii greatly varies among regions and correlates with the socio-economic conditions and the presence of infection risk factors [44], the reported seropositivity in the presented study could be influenced by such aspects.…”
Section: Discussioncontrasting
confidence: 77%
“…The seropositivity rate recorded in this study was lower than that in HIV-positive patients from Slovakia examined in 2019 (34.4%) [43], and also lower than the pooled prevalence of latent toxoplasmosis calculated for Europe (41.1%) in the systematic review of studies published by Rostami et al [44]. Since the seropositivity to T. gondii greatly varies among regions and correlates with the socio-economic conditions and the presence of infection risk factors [44], the reported seropositivity in the presented study could be influenced by such aspects.…”
Section: Discussioncontrasting
confidence: 77%
“…Reactivation of chronic T. gondii infection in HIVinfected persons is most often connected with encephalitis with focal neurological abnormalities, sometimes with fever, defects of the visual field, and defects of cerebellum function, with neuropsychiatric symptoms. The extra cerebral form can also occur, mostly presented as chorioretinitis with multifocal and bilateral lesions of the optic nerve [67]. Therefore, study the disease as an opportunistic infection is critical.…”
Section: Discussionmentioning
confidence: 99%
“…The result was logic, as in AIDS patients; the immunity will be less than usual. Human immunodeficiency virus (HIV) infection encompasses an acute phase that lasts for months, followed by a clinically latent phase that typically lasts for a few years and, ultimately, by the collapse of the immune system that characterizes acquired immunodeficiency syndrome [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of long-term survival rate of patients after HSCT, CMVR related severe vision loss compromised quality of life in these patients [13][14][15][16] . Although several studies reported the clinical features and prognosis of CMVR, most of them focused on HIV-positive patients [17][18][19][20] . Researches for the long-term follow-up (more than 6mo) prognosis of HIV-negative CMVR patients were limited.…”
Section: Introductionmentioning
confidence: 99%